Ketepatan Pengkodean Diagnosis Demam Berdarah Dengue Berdasarkan Hasil Pemeriksaan Klinis di Rumah Sakit Singaparna Medika Citrautama - Ari Sukawan (Poltekkes Kemenkes Semarang, 2024)
One of the supporting units in the hospital, namely medical records, is a manual / electronic record carried out by health care providers such as diagnosis. One of the medical record activities is to code the disease. Coding is the provision of alphanumeric symbols carried out by the coder. The diagnosis coding provided must be correct in accordance with the codes listed in ICD-10, the correct coding will affect hospital health financing. The research was conducted at Medika Citra Utama Hospital. This study aims to describe the coding procedures and accuracy of disease diagnosis using a cross sectional design. The population of cases in this study were medical records of dengue haemorrhagic fever patients from January to December 2022. The number of samples was 98 medical records. The sampling technique used was simple random sampling. The results of the study of diagnosis coding procedures carried out by the coder have not been in accordance with the steps that have been determined by ICD-10 volume 2 due to the busyness of officers in carrying out other activities and there are 78.6% of medical records that are appropriate and in accordance with the results of clinical examinations, 21.4% of medical records that are not appropriate and do not match the results of clinical examinations resulting in pending claims at the hospital. The conclusion of this study is that coder officers are expected to do coding referring to ICD-Volume 2 and pay attention to clinical examination in order to get accurate coding so that hospital claims are claimed on time.